Length of stay for patients undergoing invasive electrode monitoring with stereoelectroencephalography and subdural grids correlates positively with increased institutional profitability. (20th April 2017) - Chan, Alvin Y.; Kharrat, Sohayla; Lundeen, Kelly; Mnatsakanyan, Lilit; Sazgar, Mona; Sen‐Gupta, Indranil; Lin, Jack J.; Hsu, Frank P. K.; Vadera, Sumeet
Summary: Objective: Lowering the length of stay (LOS) is thought to potentially decrease hospital costs and is a metric commonly used to manage capacity. Patients with epilepsy undergoing intracranial electrode monitoring may have longer LOS because the time to seizure is difficult to predict or control. This study investigates the effect of economic implications of increased LOS in patients undergoing invasive electrode monitoring for epilepsy. Methods: We retrospectively collected and analyzed patient data for 76 patients who underwent invasive monitoring with either subdural grid (SDG) implantation or stereoelectroencephalography (SEEG) over 2 years at our institution. Data points collected included invasive electrode type, LOS, profit margin, contribution margins, insurance type, and complication rates. Results: LOS correlated positively with both profit and contribution margins, meaning that as LOS increased, both the profit and contribution margins rose, and there was a low rate of complications in this patient group. This relationship was seen across a variety of insurance providers. Significance: These data suggest that LOS may not be the best metric to assess invasive monitoring patients (i.e., SEEG or SDG), and increased LOS does not necessarily equate with lower or negative institutional financial gain. Further research into LOS should focus on specific specialties, as each may differ in terms of financial implications.